Localized delivery of methylprednisolone sodium succinate with polymeric nanoparticles in experimental injured spinal cord model. (17th November 2017) - Karabey-Akyurek, Yasemin; Gurcay, Ahmet Gurhan; Gurcan, Oktay; Turkoglu, Omer Faruk; Yabanoglu-Ciftci, Samiye; Eroglu, Hakan; Sargon, Mustafa Fevzi; Bilensoy, Erem; Oner, Levent
Abstract: With important social and economic consequences, spinal cord injuries (SCIs) still exist among major health problems. Although many therapeutic agents and methods investigated for the treatment of acute SCI, only high dose methylprednisolone (MP) is being used currently in practice. Due to the serious side effects, high dose systemic MP administration after SCI is a critical issue that is mostly considered controversial. In our study, it is aimed to develop a nanoparticle-gel combined drug delivery system for localization of MP on trauma site and eliminating dose-dependent side effects by lowering the administered dose. For this purpose, methyl prednisolone sodium succinate (MPSS) loaded polycaprolactone based nanoparticles were developed and embedded in an implantable fibrin gel. The effects of MPSS delivery system are evaluated on an acute SCI rat model, by quantification the levels of three inflammatory cytokines (interleukin-1β, interleukin-6 and caspase-3) and assessment of the damage on ultrastructural level by transmission electron microscopy. Developed NP-gel system showed very similar results with systemic high dose of MPSS. It is believed that developed system may be used as a tool for the safe and effective localized delivery of several other therapeutic molecules on injured spinal cord cases.